Pengaruh Konten Prank ojek Online di Youtube Terhadap tingkat kecemasan Driver - Luthfi Hadyan Yulizar; Salman (UNIVERSITAS KALBIS, 2022)
Content Prank Online Driver recently uploaded to social media YouTube. This research purposed to figure out impact of YouTube content prank online driver towards on level anxiety online driver, and this research implemented in Jl. Tebet Timur South Jakarta. Researcher used Stimulus Respons Theory and used positivism paradigm. Method in this research is description survey which are given to random sampling. Subjects in this research are 222 online driver on Tebet Timur Street, South Jakarta. The result of this research shows that 222 respondence if content prank online driver in YouTube towards on level of their anxiety, which proven by value of “Persamaan Regresi Sederhana” Y= 7,200 + 0,422X and T-hitung = 13,357 > T-tabel = 1,652 and amount of contribution from conten prank online driver up to 44,8% or 0,448. In the same time, content prank online driver on YouTube shows that online driver feels so worried.